Analysis of complete genome sequences of G9P[19] rotavirus strains from human and piglet with diarrhea provides evidence for whole-genome interspecies transmission of nonreassorted porcine rotavirus - Arpaporn Yodmeeklin (2018)
© 2016 Whole genomes of G9P[19] human (RVA/Human-wt/THA/CMH-S070-13/2013/G9P[19] ) and porcine (RVA/Pig-wt/THA/CMP-015-12/2012/G9P[19]) rotaviruses concurrently detected in the same geographical area in northern Thailand were sequenced and analyzed for their genetic relationships using bioinformatic tools. The complete genome sequence of human rotavirus RVA/Human-wt/THA/CMH-S070-13/2013/G9P[19] was most closely related to those of porcine rotavirus RVA/Pig-wt/THA/CMP-015-12/2012/G9P[19] and to those of porcine-like human and porcine rotaviruses reference strains than to those of human rotavirus reference strains. The genotype constellation of G9P[19] detected in human and piglet were identical and displayed as the G9-P[19]-I5-R1-C1-M1-A8-N1-T1-E1-H1 genotypes with the nucleotide sequence identities of VP7, VP4, VP6, VP1, VP2, VP3, NSP1, NSP2, NSP3, NSP4, and NSP5 at 99.0%, 99.5%, 93.2%, 97.7%, 97.7%, 85.6%, 89.5%, 93.2%, 92.9%, 94.0%, and 98.1%, respectively. The findings indicate that human rotavirus strain RVA/Human-wt/THA/CMH-S070-13/2013/G9P[19] containing the genome segments of porcine genetic backbone is most likely a human rotavirus of porcine origin. Our data provide an evidence of interspecies transmission and whole-genome transmission of nonreassorted G9P[19] porcine RVA to h uman occurring in nature in northern Thailand.